Impact Assessment of Sex Offender Notification on Wisconsin Communities, 1998 - Zevitz, Richard ([Verlag nicht ermittelbar], 2001)
In response to widespread public concern about convicted sex offenders being returned from prison, federal and state laws have been passed authorizing or requiring the notification of local communities where sex offenders would be living. The dilemma associated with community notification is balancing the public's right to be informed with the need to successfully reintegrate offenders within the community. Wisconsin was one of the 50 state jurisdictions that enacted a sex offender community notification statute. This project was an in-depth study of that state's experience from the vantage point of several groups affected by the community notification process. This data collection contains three surveys that were conducted from January 1998 through mid-September 1998: (1) a survey of 704 neighborhood residents at 22 community notification meetings throughout the state (Part 1), (2) a statewide survey of 312 police and sheriff agencies (Part 2), and (3) a statewide survey of 128 probation and parole agents and their supervisors from units with sex offender caseloads (Part 3). Variables in Part 1 include how respondents found out about the date and place of the community notification meeting, respondents' opinions of the purpose of the meeting, how clearly the purpose of meeting was stated, how the meeting went, outcomes, rating of information presented, if materials were handed out, if the materials were helpful, and respondents' level of concern after the meeting. Enforcement agency data (Part 2) include variables such as type of agency, type of jurisdiction, population size, if the agency designated a special staff member to coordinate the sex offender registration and notification functions, if the agency had policies regarding registration of sex offenders and community notification about sex offenders, if the agency attended statewide training, who participated in the Core Notification Team, what kind of information was used to determine a sex offender's risk to the community, which agencies registered to receive notice, and if the agency planned to update or expand their notification list. Additional variables cover the number of requests for information from Neighborhood Watch Programs, what identifying information about the offender the agency released, types of communication the agency received from the public after a notification had been issued, topics discussed in the public communication to the agency, benefits of the community notification law, difficulties in carrying out the requirements of the law, and methods developed to handle the problems. Probation and parole survey (Part 3) variables focused on characteristics of the respondent's supervising area, the number of agents assigned to the respondents' unit, the number of agents designated as Sex Offender Intensive Supervision Program (SO-ISP) agents or SO-ISP back-up agents, the number of child or adult sex offenders under probation or parole, if the respondent participated in any meetings regarding the provisions of the notification law and its implementation, if the supervisor received specialized training, and areas covered in the training. Other variables include whether the notification level was decided by the Core Notification Team, difficulties the respondent had with Special Bulletin Notification (SBN) offenders assigned to his/her caseload, if the respondent's field unit utilized SO-ISP or "high risk" agent teams to manage sex offenders, which individuals worked with the respondent's team, the type of caseload the respondent supervised, the number of sex offenders on the respondent's caseload, if the respondent used a special risk assessment or classification instrument for sex offenders, other information used to determine the supervision level for a sex offender, if child sex offenders were managed differently than other sex offenders, how often a polygraph was used on sex offenders, who paid for the polygraph, who chose the treatment provider, the number of supervision contacts with high-risk, SBN, or medium-risk sex offenders per week, victim policies and procedures used, rules or policies regarding revocation, and prerevocation sanctions used.